Electrical Properties of Li-based NASICON Structured Ceramic Electrolytes Substituted With Chromium - A. Mustaffa, N.; S. Mohamed, N.; ., . (International Journal of Engineering and Technology, 2019)
Electrical properties of Li - ion conducting Li1+xCrxSn2-x(PO4)3 ceramic electrolytes with 0 < x < 1 were studied using electrical impedance spectroscopy in the frequency range of 1 Hz to 10 MHz at room temperature. Impedance analysis showed an increase in bulk and grain boundary conductivity with the increment of x up to x = 0.7. The highest bulk and grain boundary conductivity were 6.52 Ã—10-6 S cm-1 and 1.62 Ã—10-6 S cm-1 in the system of Li1.7Cr0.7Sn1.3(PO4)3 at room temperature. The charge carrier concentration, Â Â mobile ion concentration, ionic hopping rate and ionic mobility were calculated by fitting the AC conductivity spectra. The ionic hopping rate and ionic mobility of the compound increased with the substitution of chromium due to the extra interstitial Li+ ions in the system.Â Additionally, the highest conducting sample with x = 0.7 had a negligible electronic conductivity based on transference number measurements. These results imply that the Li1+xCrxSn2-x(PO4)3 electrolytes obtained in this work can be considered as future candidates for solid state electrolytes.Â Â